The Role of Mycobacterium Tuberculosis Detection on Oral Mucosa in Diagnosis of Pulmonary Tuberculosis - Bakti, Reiska Kumala; Soebadi, Bagus; Ernawati, Diah Savitri; Mertaniasih, Ni Putu Made (Faculty of Dental Medicine Universitas Airlangga, 2023)
Background. Tuberculosis is one of the world's health problems, with larger mortality rate than HIV/AIDS. In order to control this disease, a new and inexpensive diagnostic method is needed. Oral samples, such as buccal mucosa epithelium, can be an alternative specimen, other than sputum, in the diagnosis of tuberculosis. Purpose. This study aimed to analyze the presence of Mycobacterium tuberculosis on buccal swabbing of tuberculosis patients. Method. Study was conducted on 18 new pulmonary tuberculosis patients in TB DOTS unit of Dr. Soetomo General Hospital. Each subject was swabbed on the buccal mucosa of the oral cavity for subsequent examination of PCR, AFB, and culture to detect Mycobacterium tuberculosis in the oral cavity. Result. The results showed that Mycobacterium tuberculosis was detected from 2 study subjects (11%) using PCR, whereas in AFB and culture examination methods no Mycobacterium tuberculosis was detected on buccal mucosa of the oral cavity. Conclusion. This study showed that Mycobacterium tuberculosis was detected on buccal mucosa swab of tuberculosis patients based on PCR technique, but this method is less suitable in diagnosis of pulmonary tuberculosis.